Development and progress for three decades in umu test systems. (December 2016) - Oda, Yoshimitsu
Abstract Umu test have been widely used to predict the detection and assessment of DNA- damaging chemicals in environmental genotoxicity field for three decades. This test system is more useful with respect to simplicity, sensitivity, rapidity, and reproducibility. A review of the literature on the development of theumu test is presented in this article. The contents of this article are included a description of numerous data using theumu test. This test have been fully evaluated and used in many directions. Different genetically engineeredumu systems introducing bacterial and rat or human drug metabolizing enzymes into theumu tester strains, have been successfully established and are considered as useful tools for genotoxicity assays to study the mechanisms of biotransformation in chemical carcinogenesis. Actually, we developed that two types of bacterial metabolizing enzymes and 4 types of rat and human metabolizing enzyme DNAs are expressed in these strains such as nitroreductase andO -acetyltransferase, cytochrome P450, N -acetyltransferases, sulfotransferases, and glutathioneS -transferases, respectively. Due to increasing numbers of minute environmental samples and new pharmaceuticals, a high-throughputumu test system usingSalmonella typhimurium TA1535/pSK1002, NM2009, and NM3009 strains provides a useful for these genotoxicity screening. I also briefly describe the first attempts to incorporate suchumu tester strain into photo-genotoxicity test.